Robustness of coherence: an operational and observable measure of quantum coherence - Napoli, Carmine; Bromley, Thomas R.; Cianciaruso, Marco; Piani, Marco; Johnston, Nathaniel; Adesso, Gerardo (American Physical Society, 2016)
Quantifying coherence is an essential endeavour for both quantum foundations and quantum technologies. Here the robustness of coherence is defined and proven a full monotone in the context of the recently introduced resource theories of quantum coherence. The measure is shown to be observable, as it can be recast as the expectation value of a coherence witness operator for any quantum state. The robustness of coherence is evaluated analytically on relevant classes of states, and an efficient semidefinite program that computes it on general states is given. An operational interpretation is finally provided: the robustness of coherence quantifies the advantage enabled by a quantum state in a phase discrimination task.